Areas of improvement for colorectal cancer screening: Results of a screening initiative for 10,000 health care employees in Austria - Prosenz, Julian; Österreicher, Zoe Anne; Koutny, Florian; Asaturi, Arno; Birkl, Moira; Hanke, Rosanna; Ferlitsch, Monika; Maieron, Andreas (Endoscopy International Open, 2024)
Background and study aims Participation in and quality of colorectal cancer (CRC) screening varies greatly and it is unclear how much of CRC screening guideline quality metrics reach patients. The aims of this prospective observational study were to provide data from everyday practice in Austria.Patients and methods All employees aged ≥ 50 years were invited and received a stool-based-test (FIT (cut-off 25 mcg Hb/g) and M2PK), which could be dropped off at the workplace. All individuals with positive tests were called and offered a colonoscopy near their workplace/home in ≤ 3 weeks performed by unselected endoscopists. Non-attendees received email and telephone reminders.Results Of 10,239 eligible employees (2706 males, 7533 females), 2390 (23%) (plus 673 < 50 years) median age 53 (interquartile range 50;56) participated in the stool-based screening (18% males, 25% females). Of 3063 tests, 747 (24%) were positive. The follow-up rate for 616 individuals who accepted or eventually underwent colonoscopy was 84% (n = 517). The adenoma detection rate (ADR) was 20.5% (31% in men, 17% in women) and varied substantially, ranging from 15% in hospitals (excluding the study center) to 18.5% among office-based endoscopists, and up to 36% in the study center. Most European Society of Gastrointestinal Endoscopy-recommended performance indicators were unmet, including the polyp detection rate (PDR), ADR, reporting of polyp characteristics, and bowel preparation adequacy.Conclusions There is a serious gap between recommended standards and real-world CRC screening colonoscopy quality. Implementation of CRC screening should not only be accompanied by strategies to increase participation rates but focus on implementation of rigorous, mandatory colonoscopy quality assurance programs.
Keywords: Endoscopy Lower GI Tract; Polyps/adenomas/...; CRC screening; Quality and logistical aspects; Quality management; Performance and complications